Early initiated noradrenaline versus fluid therapy for hypotension and shock in the emergency department (VASOSHOCK): a protocol for a pragmatic, multi-center, superiority, randomized controlled trial - Lasse Paludan Bentsen; Thomas Strøm; Jakob Lundager Forberg; Gerhard Tiwald; Peter Biesenbach; Malik Kalmriz; Jens Henning Rasmussen; Nikolaj Raaber; Sören Möller; Mette Løkke; Gitte Boier Tygesen; Hanne Nygaard; et al. (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background Shock is a condition with high mortality even with early intervention and treatment. Usual care for shock and hypotension in the Emergency Department (ED) is intravenous fluid resuscitation which can lead to fluid overload and other complications. When fluid therapy fails or risk of complications are high, the next treatment step is the use of vasopressors for stabilisation. Noradrenaline therapy for hypotension and shock are commonly used in ED’s outside Scandinavia, but the evidence on the optimal initiation time is sparse. The lack of noradrenaline therapy in Scandinavia provides a unique environment to investigate the possible implications of early initiation. The aim of this trial is to investigate whether the use of early initiated noradrenaline compared to ED fluid therapy can improve blood pressure goals and by that, reduce the need for ICU admittance. Methods This protocol describes a pragmatic, multi-center, superiority randomized controlled trial, randomizing patients with hypotension to intervention or control. Eligible patients are ≥ 18-year-old who have received at least 500 ml intravenous fluids (including prehospital administration), and without suspected cardiogenic, haemorrhagic, anaphylactic, or neurogenic causes, or require direct ICU admittance due to non-hemodynamic severe organ failure. The intervention group receives noradrenaline initiated at 0.05 mcg/kg/min with a maximum of 0.15 mcg/kg/min through a peripheral venous catheter for up to 24 h. The control group receives usual care. Treatment is targeted for a systolic blood pressure ≥ 100 mmHg, a mean arterial pressure ≥ 65 mmHg or a clinician defined blood pressure target. We require a sample size of 320 patients to show a significant difference in proportion of patients achieving shock control within 90 min (primary endpoint). Key secondary outcomes include ICU free days alive within 30-days and 30-day all-cause mortality. Discussion Previous prospective randomized trials on early peripheral noradrenaline treatment for shock are sparse and are investigated in settings where noradrenaline use is already usual care. Since noradrenaline are not used as standard treatment for shock in Scandinavian EDs, this provides a unique opportunity not only to investigate the early initiation of noradrenaline for shock, but also comparing it directly to ED fluid only approach. Trial registration: EU CT ID 2023-504584-16-00. ClinicalTrials.gov NCT05931601. URL: https://classic.clinicaltrials.gov/ct2/show/NCT05931601